Financial Inclusion and Poverty Reduction in Remote Regions: Evidence from Lanny Jaya Regency, 2022–2023 - Wenda, Yusuf; Mollet, J.; Hutajulu, Halomoan (Journal of Regional Economics and Development, 2025)
Financial inclusion has increasingly been positioned as a strategic instrument for accelerating poverty reduction, particularly in geographically isolated regions where formal financial access remains limited. This study examines the relationship between financial inclusion and poverty in Lanny Jaya Regency, Papua Highlands, during the period January 2022–December 2023. Using a mixed-methods design, monthly secondary data (N = 24) on poverty rate, bank account ownership, availability of banking service points, electronic money usage, and financial literacy were analyzed using descriptive statistics and simple linear regression, complemented by qualitative field observations and interviews. The results show a consistent decline in the poverty rate from 28.5% to 22.8% alongside significant improvements in financial inclusion indicators: account ownership (32.1%→46.5%), banking outlets (4→10 units), e-money users (8.3%→19%), and financial literacy (55.2%→66%). Regression analysis confirms a strong and statistically significant negative relationship between financial inclusion and poverty (β = –0.518; R² = 0.998; p < 0.001). The findings demonstrate that enhanced access and utilization of formal financial services contribute to poverty reduction, although structural barriers such as geographical isolation, low digital readiness, and product–user mismatch persist. Policy implications emphasize expanding last-mile financial infrastructure, context-specific credit products, and community-based financial literacy programs.